Feasibility of using WHO's e-mhGAP-IG Mobile Application for Child and Adolescent Mental/Behavioral Disorders and Substance Use in Indian Setting: Protocol paper - Koni, Kiranmayi; Tarugu, Jayanthi; Chaudhuri, Sirshendu; Srinivasan, Muthuvenkatachalam; AM, Krishna (National Journal of Community Medicine, 2024)
Background: The treatment gap for people with common mental disorders is large, estimated to be 75–95% in India; the reasons are multi-factorial. It was found that 89% of the primary health centers are not providing mental health care services. Technology like the electronic-mental Health Global Action Program-Intervention Guide (e-mhGAP-IG) is necessary to fill this gap, which in turn helps to attain one of the aims of National Mental Health Program-1982. Hence, the study is planned to understand the feasibility and adaptability of WHO’s e-mhGAP-IG by the primary health workers in the delivery of mental health care for child and adolescent mental/behavioral disorders (CMH) and substance use disorders (SUB). Methods: It is an open-label randomized control trial planned to conduct at primary healthcare centers, Chittoor district. Primary health care staff working at PHCs/Sub-centers having one year experience, and being able to handle smart phones will be included in the study. Data will be collected using a self-structured case report form (CRF) and analyzed by applying per protocol analysis using JAMOVI software. The cost of intervention and the impact on disease outcomes will be taken concurrently to estimate the cost-effectiveness of the intervention. Trial registration: CTRI/2023/04/051899 dated 24/04/2023 under the clinical trials registry-India Protocol version: 1.0 dated 24/04/2023